Intracranial phosphaturic mesenchymal tumors. A case report and review of literature. Issue 5 (26th July 2022) - Kojima, Daijiro; Ohba, Shigeo; Abe, Masato; Suzuki, Atsushi; Horibe, Seiji; Tateya, Ichiro; Hasegawa, Mitsuhiro; Hirose, Yuichi
Abstract : Most osteomalacia‐inducing tumors (OITs) are phosphaturic mesenchymal tumors (PMTs) that secrete fibroblast growth factor 23 (FGF23). These tumors usually occur in the bone and soft tissues, and intracranial OITs are rare. Therefore, intracranial OIT is difficult to diagnose and treat. This paper presents a case of intracranial OIT and shows a review of previous cases. A 45‐year‐old man underwent nasal cavity biopsy and treatment with active vitamin D3 and neutral phosphate for hypophosphatemia. Amplification of FGF23 mRNA level within the tumor was detected. Subsequently, the surgical specimen was diagnosed with a PMT and was considered the cause of the patient's osteomalacia. The patient was referred to a neurosurgery department for the excision of the intracranial tumor extending to the nasal cavity. After tumor removal, the serum levels of FGF23 and phosphorus were normalized as compared to preoperative those. The patient remains disease‐free, without additional treatment, approximately 10 years after surgery, with no tumor recurrence. As per the literature, intracranial OITs usually occur in patients aged 8–69 years. Bone and muscle pain are major complaints. Approximately 60% of the patients reported previously had symptoms because of intracranial tumors. In some cases, it took several years to diagnose OIT after the onset of the osteomalacia symptoms. Laboratory data in such cases show hypophosphatemia and elevated FGF23 levels. Because FGF23 levels are associated with the severity of osteomalacia symptoms, total tumor resection is recommended. PMT and hemangiopericytoma (HPC) are histologically similar, but on immunochemistry, PMT is negative for signal transducer and activator of transcription 6 (STAT6), whereas HPC is positive. FGF23 amplification is seen in PMTs but not in HPCs. Therefore, the analysis of FGF23 and STAT6 was helpful in distinguishing PMTs from HPCs. In cases of hypophosphatemia and osteomalacia without a history of metabolic, renal, or malabsorptive diseases, the possibility of oncogenic osteomalacia should be considered.